Sharia Marketing Mix: A Model of Digital Marketing Management Strategy of Zakat - Utami, Pertiwi; Basrowi, Basrowi (Mabsya: Jurnal Manajemen Bisnis Syariah, 2021)
Zakat institutions make a variety of new innovations and accelerations in terms of management strategies to improve zakat management. Getting support from Government Regulations and DSN MUI Fatwa regarding the use of IT is certainly a motivation for zakat institutions to increasingly actively develop technology-based services. IT is one of the main focuses of the marketing strategy to increase muzaki's interest in distributing zakat through online zakat services. But in the middle of the community it seems that the presence of digital zakat services still requires a long process of obtaining 'postioning'. In addition, the use of technology must also be more careful, especially because of the negative impact it has. Sharia marketing mix offers strategy management based on sharia principles which in its development is dominated by contemporary fiqh studies. The research aims to provide a literature review on the collaboration of sharia marketing mix and digital marketing zakat. An interesting study considering there are still few studies that reveal a combination of both. Sharia marketing mix present offers management strategies that conventional marketing mix lacks. The results of the literature review state that sharia marketing mix has a special advantage in filtering the negative impact of the use of technology compared to the marketing mix which has been widely used by companies, financial institutions and non-banks.